Comparison of nasal sprays and irrigations in the delivery of topical agents to the olfactory mucosa. (28th June 2013) - Lam, Kent; Tan, Bruce K.; Lavin, Jennifer M.; Meen, Eric; Conley, David B.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Sinonasal diseases are often treated with topical agents administered through various application techniques, but few prior studies have examined their distribution to the olfactory mucosa. The purpose of this study was to compare the distribution of nasal irrigations to sprays within the olfactory cleft. Study Design Human cadaveric study. Methods Eight cadaveric heads, providing a total of 15 nasal sides, underwent treatment with methylene blue solution. Application utilized a pressurized spray device followed by an irrigation squeeze bottle, both used according to manufacturer instructions. Videos and images from six standardized anatomical positions were recorded by rigid nasal endoscopy prior to and following each method of agent delivery. Using the acquired images, three reviewers blinded to the means of application scored the approximate surface area stained. An image‐analysis program was additionally calibrated and used to measure pixel intensity in order to quantify surface delivery of methylene blue. Results Based on both blinded reviewer ratings and image pixel intensity measurements, irrigations demonstrated a greater extent and intensity of staining than sprays within the sphenoethmoid recess, superior turbinate, and superior olfactory cleft (all P < 0.05). Sprays and irrigations, however, were comparable in the extent of staining at the nasal vestibule (P > 0.05), inferior turbinate (P = 0.04), and middle turbinate (P > 0.05). Conclusions Compared to sprays, irrigations provide a more effective method of delivering topical agents to the posterior and superior aspects of the nasal cavity. The thorough distribution of irrigations has important clinical implications for improving the delivery of therapeutic agents to the olfactory mucosa. Level of Evidence N/A. Laryngoscope, 123:2950–2957, 2013